Facile synthesis of Y2S3/ZnO nanocomposite and its catalytic performance in the degradation of Methylene Blue using UV-A/solar illumination. (August 2016) - Senthilraja, A.; Krishnakumar, Balu; Nawabjan, Shaik Abdullah; Sobral, Abilio J.F.N.; Subash, B.; Swaminathan, M.; Shanthi, M.
Graphical abstract: Highlights: A simple method adopted for the synthesis of novel Y2 S3 /ZnO. Y2 S3 /ZnO nanocomposite has a large potential for industrial effluent treatment. Y2 S3 /ZnO is more efficient at neutral pH than prepared and commercial catalysts. Abstract: Y2 S3 /ZnO nanocomposite synthesized by a facile precipitation method combined with a mild ultrasonic technique. Y2 S3 /ZnO was characterized using X-ray diffraction (XRD), Scanning electron microscopy (FE-SEM), Elemental colour mapping, Transmission electron microscopy (TEM), UV–vis diffuse reflectance spectroscopy (UV–vis DRS), Photoluminescence spectroscopy (PLS), X-ray photoelectron spectroscopy (XPS) and BET surface area measurements. Photocatalytic activity of Y2 S3 /ZnO was evaluated by the degradation of Methylene Blue (MB, an organic dye) as a model pollutant using UV-A/solar light. The 10.1 wt% Y2 S3 /ZnO degraded dye completely within 60 min at neutral pH 7. It is more efficient than bare ZnO, commercial ZnO, TiO2 -P25 and TiO2 (Aldrich). The superior photocatalytic performance of 10.1 wt% Y2 S3 /ZnO is attributed to high UV-A/solar light absorption as well as effective charge carrier separation. A possible mechanism of photocatalysis is proposed. This novel composite material has potential applications in the industrial effluent treatment at the neutral pH 7.